Role of TNF-α in the Mechanisms Responsible for Preterm Delivery Induced by Stx2 in Rats - Burdet, Juliana (2013)
Shiga toxin-producing Escherichia coli (STEC) infections could be one of the causes of fetal morbimortality in pregnant women. We have previously reported that Shiga toxin type 2 (Stx2) causes preterm delivery in pregnant rats. In this study, we evaluate the role of tumor necrosis factor alpha (TNF-α), prostaglandins (PGs), and nitric oxide (NO) in the Stx2induced preterm delivery.